Penguatan Kemampuan Literasi Finansial Anak di Sekolah Dasar Negeri Terrak 1 Pamekasan - Arifin, Samsul; Kamila Novita, Tsurayya (Al-Khidmah: Jurnal Pengabdian Kepada Masyarakat, 2025)
This study aims to enhance the financial literacy skills of elementary school students by integrating financial literacy programs into the curriculum at SD Terrak 1 Pamekasan. Financial literacy is deemed essential for preparing students to face future economic challenges through the introduction of key financial management concepts: earning, saving, spending, and donating. Employing a qualitative approach with a descriptive case study design, data were collected through in-depth interviews, participatory observations, and document analysis involving fifth-grade students and teachers as primary informants. The findings indicate that the implementation of the financial literacy program has successfully improved students’ understanding and skills in managing personal finances. Students gained practical experience through entrepreneurial simulations, habitual saving, budget planning, and donation activities that integrate social and ethical values. The use of interactive learning media such as videos, books, and educational games further supported the teaching and learning process, enabling a more concrete comprehension of financial concepts. The study underscores the importance of aligning educational policies, curriculum content, and community involvement to sustain financial literacy education. Therefore, it is recommended that this program be systematically integrated into the national curriculum to foster entrepreneurial character and enhance the financial readiness of future generations.